Anatomic and Histological Investigation of the Anterolateral Capsular Complex in the Fetal Knee. (May 2017) - Sabzevari, Soheil; Rahnemai-Azar, Amir Ata; Albers, Marcio; Linde, Monica; Smolinski, Patrick; Fu, Freddie H.
Background: There is currently disagreement with regard to the presence of a distinct ligament in the anterolateral capsular complex of the knee and its role in the pivot-shift mechanism and rotatory laxity of the knee. Purpose: To investigate the anatomic and histological properties of the anterolateral capsular complex of the fetal knee to determine whether there exists a distinct ligamentous structure running from the lateral femoral epicondyle inserting into the anterolateral tibia. Study Design: Descriptive laboratory study. Methods: Twenty-one unpaired, fresh fetal lower limbs, gestational age 18 to 22 weeks, were used for anatomic investigation. Two experienced orthopaedic surgeons performed the anatomic dissection using loupes (magnification ×3.5). Attention was focused on the anterolateral and lateral structures of the knee. After the skin and superficial fascia were removed, the iliotibial band was carefully separated from underlying structures. The anterolateral capsule was then examined under internal and external rotation and varus-valgus manual loading and at different knee flexion angles for the presence of any ligamentous structures. Eight additional unpaired, fetal lower limbs, gestational age 11 to 23 weeks, were used for histological analysis. Results: This study was not able to prove the presence of a distinct capsular or extracapsular ligamentous structure in the anterolateral capsular complex area. The presence of the fibular collateral ligament, a distal attachment of the biceps femoris, the entire lateral capsule, the iliotibial band, and the popliteus tendon in the anterolateral and lateral area of the knee was confirmed in all the samples. Histological analysis of the anterolateral capsule revealed a loose, hypocellular connective tissue with less organized collagen fibers compared with ligament and tendinous structures. Conclusion: The main finding of this study was that the presence of a distinct ligamentous structure in the anterolateral complex is not supported from a developmental point of view, while all other anatomic structures were present. Clinical Relevance: The inability to prove the existence of a distinct ligamentous structure, called the anterolateral ligament, in the anterolateral knee capsule may indicate that the other components of the anterolateral complex, such as the lateral capsule, the iliotibial band, and its capsule-osseous layer, are more important for knee rotatory stability.